2018
DOI: 10.3389/fphar.2018.01055
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Characterization of a New Norbormide Derived Bodipy FL-Conjugated Fluorescent Probe for Cell Imaging

Abstract: Background: Norbormide (NRB) is a selective rat toxicant endowed with vasoconstrictor activity confined to the rat peripheral arteries. In a recent work we used a fluorescent derivative of NRB (NRB-AF12), obtained by coupling the NBD fluorophore to the parent molecule via a linker, in order to gain information about the possible site of action of the unlabeled compound. We found that NRB-AF12 labeled intracellular organelles in both NRB-sensitive and -insensitive cells and we accordingly proposed its use as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…These data show that both compounds, but particularly NRB MC009 , can be used to visualize and distinguish most organs/tissues of the dissected living larvae, and allow good definition of their intracellular structures. In addition, the co-localization studies revealed that both NRB MC009 and NRB ZLW0047 labelled subcellular organelles, that they preferentially targeted the ER and mitochondria, and that they were totally absent from the nuclei, plasma membranes and lysosomes, which is in agreement with data reported in mammalian cell studies [6]. Moreover, the efficiency of the probes was tested with two different approaches: 1) in combination with commercially available dyes for live imaging, and 2) together with green fluorescent proteins that label specific cellular structures.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These data show that both compounds, but particularly NRB MC009 , can be used to visualize and distinguish most organs/tissues of the dissected living larvae, and allow good definition of their intracellular structures. In addition, the co-localization studies revealed that both NRB MC009 and NRB ZLW0047 labelled subcellular organelles, that they preferentially targeted the ER and mitochondria, and that they were totally absent from the nuclei, plasma membranes and lysosomes, which is in agreement with data reported in mammalian cell studies [6]. Moreover, the efficiency of the probes was tested with two different approaches: 1) in combination with commercially available dyes for live imaging, and 2) together with green fluorescent proteins that label specific cellular structures.…”
Section: Resultssupporting
confidence: 90%
“…In fact, besides the well-known actin and myosin filaments and their associated proteins, muscles also contain a cytoskeleton, intracellular organelles of the endo-lysosomal pathway, and well-defined endoplasmic reticulum and mitochondrial networks [25]. We focused on these particular structures because we recently showed that they contained a significant density of binding sites for NRB MC009 [6]. To study the intracellular localization of NRB MC009 we co-loaded it into larval muscle with organelle-specific red fluorescent dyes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data show that both compounds, but particularly NRB MC009 , can be used to visualize and distinguish most organs/tissues of the dissected living larvae, and allow good definition of their intracellular structures. In addition, the co-localization studies revealed that both NRB MC009 and NRB ZLW0047 labelled subcellular organelles, that they preferentially targeted the ER and mitochondria, and that they were totally absent from the nuclei, plasma membranes and lysosomes, which is in agreement with data reported in mammalian cell studies (6). Moreover, the efficiency of the probes was tested with two different approaches: 1) in combination with commercially available dyes for live imaging, and 2) together with GFP tagged protein markers that bound to specific cellular structures.…”
Section: Resultssupporting
confidence: 90%